2019
DOI: 10.1038/s41598-019-40380-5
|View full text |Cite
|
Sign up to set email alerts
|

Silver nanowires with optimized silica coating as versatile plasmonic resonators

Abstract: Metal nanoparticles are the most frequently used nanostructures in plasmonics. However, besides nanoparticles, metal nanowires feature several advantages for applications. Their elongation offers a larger interaction volume, their resonances can reach higher quality factors, and their mode structure provides better coupling into integrated hybrid dielectric-plasmonic circuits. It is crucial though, to control the distance of the wire to a supporting substrate, to another metal layer or to active materials with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 57 publications
(82 reference statements)
1
23
0
Order By: Relevance
“…The SEM and TEM images indicated that the AgNWs had a mean diameter of 41.36 ± 8.09 nm and a lattice spacing of 0.204 nm and 0.240 nm. The latter corresponding to the (200) and (111) planes of the silver nanowire, respectively [35].…”
Section: Synthesis and Characterization Of Agnwsmentioning
confidence: 99%
“…The SEM and TEM images indicated that the AgNWs had a mean diameter of 41.36 ± 8.09 nm and a lattice spacing of 0.204 nm and 0.240 nm. The latter corresponding to the (200) and (111) planes of the silver nanowire, respectively [35].…”
Section: Synthesis and Characterization Of Agnwsmentioning
confidence: 99%
“…This provides the opportunity to investigate the aggregates with vacuum-based methods such as electron spectroscopy. Furthermore, the silica shell should provide a base for further functionalization of the aggregates that allows the investigation of optical properties that are due to distance-dependent interactions with a substrate, such as energy transfer, similar to studies of plasmon effects along metal nanowires [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the application to near-field spectra of molecular aggregates, the methodology adopted in present work can be applied to other optical spectra of various systems, such as the electron energy-loss spectroscopy of silver nanowires [38]. All of these varied applications require a similar inversion as for Eq.…”
Section: Discussionmentioning
confidence: 99%